Satisfação do consumidor de ecommerce supermercadista brasileiro - Serva, João Renato Pacce Pinto (2023)
The supermarket retail market in the world had to go through strong changes to be able to aggregate to their customers during the pandemic and in Brazil it was no different. The chains had to reinvent themselves to be able to efficiently serve their customers who, at that moment, could only make their purchases online, through e-commerce. But are the customers who liked and preferred to continue with this way of consumption behavior is satisfied with the service that is being offered? To answer this question, a field research was carried out, through a questionnaire, based on the e-SQ (electronic Service Quality) parameterization model.​​ Based on eight of the eleven dimensions set by the model, adaptations were made in order to better meet the parameters of the supermarket sector's e-commerce model. The result was a questionnaire with three questions for each of the six resulting dimensions